THE ROLE OF TRANSFORMATIONAL LEADERSHIP IN ENHANCING EMPLOYEE ENGAGEMENT IN THE HYBRID WORK ERA - Fera Riske Anggita (International Journal Management and Economic, 2025)
This study aims to examine the influence of transformational leadership on employee engagement within the context of hybrid work environments. As organizations adopt flexible work models combining remote and on-site arrangements, sustaining employee motivation and involvement has become increasingly challenging. A quantitative explanatory research method was employed, using survey data collected from 102 employees working under hybrid models. The instruments used included a transformational leadership scale (MLQ) and the Utrecht Work Engagement Scale (UWES), measured through a 5-point Likert scale. Data analysis was conducted using linear regression and quadrant mapping. The results show that transformational leadership has a positive and significant effect on employee engagement (R² = 0.425; p < 0.001). Furthermore, quadrant analysis revealed that most respondents were classified as "Engaged Hybrid Teams," characterized by high leadership and engagement. However, the presence of "Leadership-Driven but Unengaged Teams" suggests that strong leadership must be complemented by adaptive strategies tailored to hybrid work challenges. This study underscores the critical role of leadership style in promoting engagement and offers practical implications for HR and organizational development in the post-pandemic workplace.